2010
DOI: 10.1590/s1517-83822010000300020
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas presence in drinking water from collective reservoirs and wells in peri-urban area in Brazil

Abstract: Aeromonas genus is considered an emerging pathogen and its presence in drinking water supplies is a reason to public health concern. This study investigated the occurrence of Aeromonas in samples from collective reservoirs and wells used as drinking water sources in a peri-urban area. A total of 35 water samples were collected from collective reservoirs and 32 from wells bimonthly, from September 2007 to September 2008. Aeromonas spp determination was carried out using a Multiple-Tube Technique. Samples were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Similar is the case with Aeromonas spp. which can cause waterborne infections like gastroenteritis and is notoriously resistant to Chlorine disinfectants [5] . Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar is the case with Aeromonas spp. which can cause waterborne infections like gastroenteritis and is notoriously resistant to Chlorine disinfectants [5] . Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas spp. in drinkig water should be of teremendous public health concern because of their ability to form toxins and biofilms [5] . Reports mention use of specific tests like Multiple tube test using alkaline peptone water and then subculture on to Ampicillin blood agar for detecting Aeromonas spp [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the European community has established a drinking water standard for Aeromonas of no more than 20 CFU/100 mL in water leaving the treatment plant and 200 CFU/100 mL in distribution systems [42]. Similarly, Aeromonas have been detected in chlorinated drinking water from distribution systems in Italy, Mexico City, Brazil, and the United States [17,18,37,43]. This shows their capacity to survive and multiply within biofilms on the surfaces of pipes [44], as well as their relative resistance to chlorination [45][46][47].…”
Section: Drinking Watermentioning
confidence: 99%
“…Recent researches showed that they are almost equally important as coliforms in water quality monitoring programs. Even more, in some countries Aeromonas are now considered better indicator of contamination than general coliforms .…”
Section: Introductionmentioning
confidence: 99%